Pengaruh Harapan Konsumen dan Harga Terhadap Keputusan Pembelian - sukrin sukrin; Abel Haryanto (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
This study aims to examine the effect of consumer expectations and prices on purchasing decisions. The sample used was 30 respondents. The data analysis technique used multiple linear regression through SPSS version 24. The results showed that consumer expectations partially had a positive and significant effect on purchasing decisions. Then the price partially has a positive and significant effect on purchasing decisions. Consumer expectations and prices simultaneously have a positive and significant effect on purchasing decisions.